Goat Milk Product Diversification through Flavor Innovation: A Case Study at Andaleh Farm, Lima Puluh Kota Regency - Suharto, El Latifa Sri; Edwin, Tevina; Utami, Yolani; Rastosari, Adisti; Ferawati (Warta Pengabdian Andalas, 2025)
The diversification of goat milk products through flavor innovation is a strategic approach to enhancing the competitiveness of local livestock commodities, especially in response to increasing market competition. Goat milk holds significant potential as a premium dairy product; however, its market penetration remains limited due to its distinctive taste and lower consumer familiarity than cow’s milk. Introducing innovative and appealing flavor variants represents a promising solution to improve consumer acceptance and broaden market reach. This community service initiative focuses on developing market-oriented goat milk products in collaboration with local farmers at Andaleh Farm, Lima Puluh Kota Regency. The program aims to strengthen farmers’ capacity in product innovation and value-added processing by providing training and technical assistance. The expected outcomes include increased product diversity, improved product quality, and enhanced branding strategies. Ultimately, this initiative seeks to stimulate local economic growth by opening new market opportunities, increasing farmer income, and positioning goat milk as a viable and competitive local product within the regional dairy industry.